2004
DOI: 10.1016/s0740-8188(04)00023-4
|View full text |Cite
|
Sign up to set email alerts
|

Children in the information technology design process: A review of theories and their applications

Abstract: This article reviews the literature on the role that children can play in the design of information technology applications intended for young users themselves. It discusses several relevant design theories -User-Centered Design, Contextual Inquiry, Participatory Design, Cooperative Inquiry, Informant Design and Learner-Centered Design -looks at usability issues in relation to design and children, and presents a number of studies in which children have been actively involved in the design both of software and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 4 publications
0
54
0
7
Order By: Relevance
“…As mentioned above, the children mainly saw themselves as providers of feedback, and their role as initiators of ideas was not recognized by them. This issue reflects the notion that the users' role in UCD is often "too little, too late" (Scaife et al 1997) and that the UCD process puts the users in a reacting role rather than an initiating one (Scaife et al 1997;Nesset and Large 2004).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…As mentioned above, the children mainly saw themselves as providers of feedback, and their role as initiators of ideas was not recognized by them. This issue reflects the notion that the users' role in UCD is often "too little, too late" (Scaife et al 1997) and that the UCD process puts the users in a reacting role rather than an initiating one (Scaife et al 1997;Nesset and Large 2004).…”
Section: Resultsmentioning
confidence: 92%
“…The user-centred design cycle (ISO 13407, 1999) implies that users can have an active role in setting the goals, refining them iteratively, and evaluating the outcomes. However, in practice user-centred design often puts heavy emphasis on user testing in the later stages of the development, thereby placing the users in a position in which they are merely reactors to suggested solutions, not initiators of ideas (e.g., Scaife et al 1997;Nesset and Large 2004). This leads to a question whether the input of users, adults and children alike, could be better valued by involving them in more varied ways (e.g., Nesset and Large 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Druin, 1999;Druin et al, 1997) have all been applied to involve children in the design process. These design theories are varying as regards the users" (adult or child) involvement and their positioning in the design process (Nesset and Large, 2004). The Cooperative Inquiry approach, in particular, has adopted traditional participatory design techniques refined to working with children and respecting children as design partners (Druin, 1999;Druin, 2002;also Garzotto, 2008).…”
Section: Related Researchmentioning
confidence: 99%
“…Over the past six years, Cooperative Inquiry has been extended and refined through a variety of projects conducted by ourselves and other researchers in Europe, Canada, and the U.S. [2,5,7,[9][10][11][12]. We have found that Cooperative Inquiry can work for diverse age groups such as 4-6 year olds [6] and 10-13 year olds [8], but that modifications are needed due to children's varying cognitive and social abilities [6,8].…”
Section: The Techniques Of Cooperativementioning
confidence: 99%